Grip force in vibration disease. - Färkkilä, Markus (Scandinavian Journal of Work, Environment & Health, 1978)
In this experiment the hand grip force of 58 persons was measured. The study was carried out during a compulsory health examination. The subjects compressed with their left hand for 5 min fluctuating maximal force and with their right hand for 1 min with maximal constant force. The results were repeated with five different levels of vibration and without vibration. Individual forces varied in the 5-min experiment from 25 to 122 N. The strongest subjects were in a group affected by white fingers, but with no claim of diminished grip force. The weakest forces were seen in the group subjectively most-affected by vibration disease. On the basis of this examination, it seems that in some workers long-term exposure to vibration causes a diminution in grip force, which is a constant phenomenon, and it does not only manifest itself during their work. During exposure to vibration the force reduced from the resting level among the subjectively most-affected lumberjacks, but not in less-affected groups or in the reference group. No vibration frequency was found to be especially disadvantageous to grip force, and it was not possible to determine the normal limits of grip force.
Keywords: 1-minute test; 5-minute test; compression force; grip force; symptom group; vibration disease